2020
DOI: 10.2352/issn.2169-4451.2020.36.75
|View full text |Cite
|
Sign up to set email alerts
|

3D Surface Structures and 3D Halftoning

Abstract: As 3D printing is becoming increasingly popular, the demand for high quality surface reproduction is also increasing. Like in 2D printing, halftoning plays an important role in the quality of the surface reproduction. Developing advanced 3D halftoning methods for 3D printing and adapting them to the structure of the surface is therefore essential for improving surface reproduction quality. In this paper, an extension of an iterative 2D halftoning method to 3D is used to apply different halftone structures on 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…The original IMCDP algorithm has been extended to 3D domain in Ref. [40] and the effect of applying variable halftone structures based on the spatial information has shown that different halftone structures could be used to control the reproduction of details [24,41]. As a next step, we are planning to develop an adaptive structure-aware 3D color halftoning algorithm, which has all the reproduction qualities of IMCDP while being aware of the color and geometry of the 3D object.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The original IMCDP algorithm has been extended to 3D domain in Ref. [40] and the effect of applying variable halftone structures based on the spatial information has shown that different halftone structures could be used to control the reproduction of details [24,41]. As a next step, we are planning to develop an adaptive structure-aware 3D color halftoning algorithm, which has all the reproduction qualities of IMCDP while being aware of the color and geometry of the 3D object.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 shows a visual example of flexibility of IMCDP in generating different halftone structures by using different Gaussian kernels in the feed-back process. Different halftone structures, produced by the IMCDP, could be combined in the same image with smooth transition [24]. The flexibility of IMCDP in generating line-halftone structures makes it a powerful algorithm to adaptively change the halftone structure according to the image content.…”
Section: Monochrome Structure-aware Imcdpmentioning
confidence: 99%
“…In Refs. [18] and [19], it has been illustrated that line halftones aligned in the same direction as the direction of the variation on the 3D surface will attenuate the waviness of the surface, while line halftones perpendicular to that will emphasize the waviness. It has also been shown that first-and second-order FM halftones might also behave differently on different 3D surface structures.…”
Section: Three-dimensional Structure-based Imcdpmentioning
confidence: 99%
“…Hence, the difference between the maximum and the minimum standard deviation of the coordinates of the surface voxels can be used as a measure/threshold to partition a surface into structural areas. Another surface worth considering is a 3D surface shape like or , where the top (or bottom) of the area is one row of surface voxels and the two sides of it, which are m × m−1 2 each, are parallel to one of the coordinate planes [18]. The standard deviation of the three coordinates of the voxels on such a surface are and that of the other two is…”
Section: Three-dimensional Structure-based Imcdpmentioning
confidence: 99%
See 1 more Smart Citation